Continuous 24-Hour Intraocular Pressure Monitoring with a Smart Contact Lens Predicts Visual Field Progression in Normal-Tension Glaucoma - Taryudi Suharyana; Agnes Mariska (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2025)
Introduction: Normal-tension glaucoma (NTG) may progress despite normal office intraocular pressure (IOP), suggesting that 24-hour IOP dynamics captured by a smart contact lens (SCL) sensor may improve risk stratification. This study evaluated whether SCL-derived nocturnal IOP parameters independently predict Humphrey 24-2 visual field (VF) progression in NTG. Methods: This prospective observational cohort enrolled 62 NTG eyes (62 patients; one eye per patient) who underwent 24-hour SCL monitoring and serial Humphrey 24-2 SITA-Standard VF testing over 24 months at a private hospital in Palembang, Indonesia. The primary outcome was VF mean deviation (MD) slope (dB/year). Multivariable linear regression and receiver operating characteristic (ROC) analysis were performed. Results: Eyes with a nocturnal IOP acrophase (n = 36) had a significantly faster MD decline (−1.24 ± 0.31 dB/year) than eyes without acrophase (n = 26; −0.42 ± 0.19 dB/year; mean difference −0.82 dB/year, 95% CI −0.97 to −0.67, p < 0.001; Cohen d = 3.20). Independent predictors of MD slope were nocturnal acrophase (β = −0.71, p < 0.001), number of long peaks (β = −0.18, p < 0.001), and baseline RNFL thickness (β = +0.034, p = 0.002); adjusted R² = 0.64. Nocturnal amplitude yielded an AUC of 0.83 (95% CI 0.74–0.91). Conclusion: SCL-derived nocturnal IOP parameters independently predict VF progression in NTG. Integration of 24-hour SCL monitoring may enhance risk stratification beyond office IOP measurement.